Pengaruh Pupuk KCl dan Jenis Pupuk kandang terhadap Pertumbuhan dan Hasil Tanaman Ubi Jalar (Ipomoea batatas L.) - achmad turmudzi; Indiyah Muwarni; Mahayu Woro Lestari (AGRONISMA, 2020)
This study aims to determine the effect of interactions between KCl fertilizer in combination with fertilizer on the growth and yield of sweet potato (Ipomea batatas L). Study using factorial RBD. Factor 1 is a dose of potassium (K) composed of three levels: K1 = 50 kg.ha-KCl, K2 = 100 kg.ha-KCl and K3 = 150 kg.ha-KCl. Factor 2 is a fertilizer (N) type consisting of three levels: P0 = no fertilizer, P1 = buffalo fertilizer, P2 = chlorine fertilizer. Each treatment was repeated 3 times with each sample of 3 sweet potato plants. According to the results of this study, applying 50 kg / ha of KCl fertilizer and buffalo fertilizer gave better results with a plant length of 166.38 cm at an age of 120 HST and 100 kg / ha of KCl fertilizer and chlorine fertilizer. The result was obtained. More leaves and about 1,350 leaves. 67 strands compared to other treatments. Applying KCl fertilizer treatment at different doses had no substantial effect on sweet potato growth and yield. Also, applying buffalo fertilizer will result in plant length, number of leaves, leaf area, weight of new stove, fresh weight of tubers, number of tubers, dry weight of stove, but no effect dry bulbs